Ex Vivo Thrombolysis to Salvage Free Flaps Using Machine Perfusion: A Pilot Study in a Porcine Model - Brouwers, Kaj; Kruit, Anne Sophie; Koers, Erik J.; Zegers, Her J. H.; Hummelink, Stefan; Ulrich, Dietmar J. O. (Journal of Reconstructive Microsurgery, 2022)
Background Mechanical evacuation of capillary thrombi in free flaps is difficult, and often requires thrombolytic therapy. Utilizing machine perfusion systems, the possibility rises to salvage free flaps ex vivo by administering high doses of thrombolytic agents. The primary aim of this pilot study in a porcine model is to investigate the feasibility of ex vivo thrombolysis using an extracorporeal perfusion machine.Methods A model of stasis-induced thrombosis was used in 12 free rectus abdominis flaps harvested from six Dutch Landrace pigs. Compromised flaps were ex vivo perfused with University of Wisconsin preservation solution and treated according to the following study groups: (1) 1 mg of tissue plasminogen activator (t-PA) as additive, (2) 3 mg of t-PA as an additive, and (3) no thrombolytic additive. Microcirculation was assessed using near-infrared fluorescence angiography.Results Pedicled abdominal flaps were created and thrombus formation was successfully induced. Eleven abdominal flaps were perfused using the modified heart-lung machine setup. Near-infrared fluorescence angiography showed delayed or no filling was noted in the control group. In comparison, the flaps which were perfused with 1 mg t-PA or 3 mg t-PA as additive showed increased fluorescence intensity curves.Conclusion This pilot study in a porcine model presents a reliable and reproductive stasis-induced thrombosis model in free flaps. By adding t-PA to a custom-made extracorporeal perfusion system, the indocyanine green fluorescence intensity curves increased of all flaps that were perfused with different dosages of t-PA as additives, indicating restoration of capillary pressure and microcirculatory inflow.
Keywords: swine; therapeutic thrombolysis; perfusion